Cultura escolar: um olhar sobre a vida na escola - Nadal, Beatriz Gomes (2008)
This study focuses on the school culture articulating the institutional and cultural perspectives which delineate it as a multidimensional and dialect reality. It is based on Lourau (1996), Castoriadis (1982) and Foucault (1979, 1987 and 1996) on the institutional field; on Ball (1996), on the organizational field; on Williams (1979, 1982 and 2002), on the culture theory; and on Viñao Frago (1995, 1998 and 2005), on school culture field. The purposes of this doctoral dissertation lies in the knowledge and comprehension of the public elementary schools culture as well as in the proposals presented in order to contribute to the transformation of the existing culture, bringing it closer to the modern education challenges. Its theoretical underpinning was obtained by a qualitative research and by cultural studies including bibliographic study, documental analysis, observation and interviews at two public elementary and middle schools located in Ponta Grossa city, Paraná State. The research was carried out during pedagogical meetings and class councils, teacher‟s daily routine of planning activities, and the management activities of the principals. Besides the schools pedagogical projects and the minutes of class councils, technical and political documents from the office of the secretary of education of the state were analyzed. These documents orient and institutionalize the work of the school institutions. The theoretical approaches were confronted with the politics to that were related and with the practical school, in agreement to Viñao Frago (1995). The collected data were organized around the axis management of the pedagogical work . It initially showed the institute action of the schools face to the resulting politics of the State, respecting them partially, attributing them formal character, loosening them or even denying them. The schools demonstrated to create own mechanisms of management, developing private styles of being related with the educational results and the routine issues. It was observed that these mechanisms has led the schools to be maintained relatively closed regarding the social context and the changes that they recognize as necessary in their local community. They have also led the schools to utilize strategies for problems solving and mode of communication that complicate their self-knowledge, reflection about their practice and, consequently, transformation. In one way, this explains the non consolidation of micro institutional movements and the maintenance of the traditional management of the pedagogical work characterized by a bureaucratic and functional nature. This tradition assumes an active position, acting like a sort of meso-micropolitic of the school, triggered maybe in order to avoid changes and/or to protect. The analyzed data also revealed that the structural strictness of the time and its use, the conditions of teacher‟s work, the absence of solid teacher education programs capable of making to emerge the existing meanings and the epistemology of the educational practice are extremely demanding factors that can bring the school transformation to a stop